Financial Performance and Earnings Management: The Moderating Role of Digital Transformation - Roy Budiharjo; Asrarul Rahman; Idayu Rahmadewi; Swarmilah Hariani; Adam Royan Dananjaya Basri (JURNAL ECONOMINA, 2026)
This study aims to examine the effect of financial performance on earnings management and the moderating role of digital transformation in this relationship. Financial performance is proxied by Return on Assets (ROA) and firm size, earnings management is measured using discretionary accruals based on the Modified Jones Model, and digital transformation is measured through a digital keyword disclosure index derived from company annual reports. The population consists of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024, with a purposive sample of 39 companies. Data analysis employs Moderated Regression Analysis (MRA) using IBM SPSS Statistics 26. The findings indicate that ROA and firm size do not significantly affect earnings management directly. Similarly, digital transformation does not moderate the relationship between ROA and earnings management. However, digital transformation significantly moderates the effect of firm size on earnings management, where large infrastructure companies with intensive digital transformation adoption exhibit a stronger tendency toward earnings management. These findings suggest that digital transformation plays a double-edged role in financial reporting governance and does not automatically reduce managerial opportunism; rather, it may generate new performance pressures that encourage earnings management in larger firms. This study contributes to the accounting literature in the digital era, particularly in understanding the interaction between digital transformation and financial reporting in the Indonesian infrastructure sector.